Lipopolysaccharides from Microcystis Cyanobacteria-Dominated Water Bloom and from Laboratory Cultures Trigger Human Immune Innate Response - Moosová, Zdena; Šindlerová, Lenka; Ambrůzová, Barbora; Ambrožová, Gabriela; Vašíček, Ondřej; Velki, Mirna; Babica, Pavel; Kubala, Lukáš (Toxins, 2019)
Massive toxic blooms of cyanobacteria represent a major threat to water supplies worldwide. Here, the biological activities of lipopolysaccharide (LPS) isolated from Microcystis aeruginosa, the most prominent cyanobacteria in water bloom, were studied. LPS was isolated from complex environmental water bloom samples dominated by M. aeruginosa, and from laboratory cultures of non-axenic as well as axenic M. aeruginosa strains PCC7806 and HAMBI/UHCC130. Employing human blood-based in vitro tests, the LPS isolated from complex water bloom revealed the priming of both major blood phagocyte population monocytes and polymorphonuclear leukocytes documented by the increased surface expression of CD11b and CD66b. This was accompanied by a water bloom LPS-mediated dose-dependent induction of tumor necrosis factor α, interleukin-1β, and interleukin-6 production. In accordance with its priming effects, water bloom LPS induced significant activation of p38 and ERK1/2 kinases, as well as NF-κB phosphorylation, in isolated polymorphonuclear leukocytes. Interestingly, the pro-inflammatory potential of LPS from the axenic strain of M. aeruginosa was not lower compared to that of LPS isolated from non-axenic strains. In contrast to the biological activity, water bloom LPS revealed almost twice higher pyrogenicity levels compared to Escherichia coli LPS, as analyzed by the PyroGene test. Moreover, LPS from the non-axenic culture exhibited higher endotoxin activity in comparison to LPS from axenic strains. Taking the above findings together, M. aeruginosa LPS can contribute to the health risks associated with contamination by complex water bloom mass.
Keywords: GPI-Linked Proteins; CD11b Antigen; přirozená imunita; pyrogeny; GPI-vázané proteiny; Cell Adhesion Molecules; Lipopolysaccharides; water bloom; leukocyty mononukleární; endotoxin; lipopolysacharidy; Antigens, CD; CD antigeny; cytokiny; molekuly buněčné adheze; cyanobacteria; antigeny CD11b; Eutrophication; Immunity, Innate; leukocytes; kultivované buňky; Leukocytes, Mononuclear; lipopolysaccharide; lidé; eutrofizace; Humans; inflammation; Microcystis; Cells, Cultured; laboratoře; Cytokines; Laboratories; Pyrogens